A global initiative on trypanosomosis control: A proposal from the global forum on agricultural research - Camus, E.; McDermott, John J.; Francois, T. le (European Union, 2003)
The Global Forum on Agricultural Research's (GFAR) mission is to mobilize the world scientific community in their effort to alleviate poverty increase food security and promote the sustainable use of natural resources. GFAR plays a role of facilitator between stakeholders, in particular scientists and donors, but is not a donor itself. This paper looks into the justification for a Global Partnership Programme (GPP) and discusses the objectives, global priorities, regional priorities, main innovations; main on-going and related activities including vaccine, genetics, diagnosis, drugs, vectors, and risk assessment analysis.